(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Dyslipidemia, particularly hypertriglyceridemia, has become an increasingly important cause of acute pancreatitis and may influence the interpretation of pancreatic enzyme measurements in clinical practice. In patients with marked lipid abnormalities, serum amylase and lipase levels do not always accurately reflect the extent of pancreatic injury, which may complicate diagnosis and early assessment. This study aimed to analyse the relationship between dyslipidemia and pancreatic enzyme concentrations in patients with acute pancreatitis treated at Thai Binh General Hospital. Materials and Methods: A hospital-based retrospective cross-sectional analytical study was conducted using medical records and routine laboratory data of adult patients diagnosed with acute pancreatitis. Demographic, clinical, and biochemical variables were collected, including serum triglyceride, total cholesterol, amylase, and lipase levels. Pancreatic enzyme concentrations were compared across triglyceride categories. Correlation analyses were performed using Pearson’s and Spearman’s coefficients, including subgroup analyses by age, sex, body mass index, and etiology. Multivariable linear regression was used to identify independent factors associated with pancreatic enzyme levels. Results: Serum amylase declined significantly with increasing triglyceride (TG) levels, decreasing from 435.6 in the normal TG group to 203.2, 158.3, 89.4, and 124.1 across the mild, moderate, high, and very high TG groups, respectively (p < 0.001). Serum lipase also differed across TG categories, although the pattern was less consistent (p = 0.044). In overall analyses, TG and total cholesterol were inversely correlated with amylase, whereas no significant correlations were observed with lipase. The inverse TG–amylase association remained evident in several subgroups, particularly among patients aged 40–59 years, both sexes, those with BMI 18.5–24.9 kg/m², and in alcohol-, gallstone-, and hypertriglyceridemia-related acute pancreatitis. However, after multivariable adjustment, TG and total cholesterol were no longer independently associated with amylase or lipase. Conclusion: Dyslipidemia, especially elevated triglyceride levels, was associated with lower serum amylase concentrations in acute pancreatitis, suggesting that hyperlipidemia may affect the biochemical presentation of the disease. These findings support a cautious interpretation of pancreatic enzyme levels, particularly amylase, in patients with marked lipid abnormalities.